The position of the dialect of Varzuga in the Russian dialect landscape - Post, Margje (Universitetet i Tromsø, 2004)
Until recently, few researchers had studied the archaic Russian dialects of the Kola Peninsula. In 2001 and 2004, slavists from the University of Tromsø carried out dialectological field work on the Ter Coast of Kola Peninsula. On our first expedition we were joined by colleagues from Moscow. In 2004, the universities of Tromsø and Bochum received funding from NFR (Norway) and DAAD (Germany) to set up a cooperation project for the study of the endangered Russian dialects around the White Sea. This autumn, dr. Christian Sappok from Bochum University combined his visit to Tromsø with a joint field work expedition to the villages of Varzuga and Kuzomen' on the Ter Coast. Our studies have so far resulted in a Master's thesis (Pétursdóttir 2003) and a range of short articles, part of which has been published in this journal (vols. 4, 5 and the present volume). In due course I hope to finish my PhD dissertation about the dialect of the village of Varzuga. In the present article I will discuss the position of the Varzuga dialect in the Russian dialect landscape.